Bimetallic Au-Ag/Al2O3 as efficient catalysts for the hydrocarbon selective reduction of NOx from lean burn engine exhaust - More, P. M.; Dongare, M. K.; Umbarkar, S. B.; Granger, P.; Dujardin, C. (Catalysis Today, 2018)
Catalytic properties of Au-Ag/Al2O3 catalysts, prepared by successive impregnation, have been investigated for the hydrocarbon selective catalytic reduction (HC-SCR) of NOx. The performances of pre-reduced and aged catalysts were evaluated on synthetic reaction mixtures with gas compositions representative of the exhaust of Diesel powered engines. An optimal 2 wt.% Ag loading was chosen and the order of introduction during sequential impregnation of Ag or Au on respectively pre-impregnated Au/Al2O3 and Ag/Al2O3 substrates was investigated revealing drastic changes on the catalytic properties after aging. XPS analysis shows a significant silver enrichment irrespective of the preparation route and aging conditions whereas ex situ UV-vis DRS analysis reveals significant electronic disturbances which reflect different interactions between Au and Ag in fresh and aged Au-Ag/Al2O3 and Ag-Au/Al2O3 catalysts. As a consequence, significant rate enhancements in NOx conversion were observed with the superior performance of Au-Ag/Al2O3 but a lower resistance to deactivation at high temperature explained by different behaviour towards redispersion/agglomeration processes highlighted from TEM observations. (C) 2016 Elsevier B.V. All rights reserved.